Integrated hepatitis e virus monitoring in central Argentina : a six-year analysis of clinical surveillance and wastewater-based epidemiology - Fantilli, Anabella Clara; Masachessi, Gisela; Di Cola, Guadalupe; Castro, Gonzalo; Sicilia, Paola; Marinzalda, María de los Angeles; Cachi, Ariana Mariela; Moreno, Claudia; Borda, Mariel; Ibarra, Gustavo; Rojas, Ricardo Manuel; Parreño, Gladys Viviana; et al. (Elsevier, 2024)
Wastewater-based epidemiology (WBE) has gained prominence worldwide as a powerful tool in public health. This study aimed to monitor the circulation of Hepatitis E Virus (HEV) from wastewater samples collected during a six-year period and compare these results with clinical surveillance in the central region of Argentina. From 2017 to 2022, 1008 raw wastewater samples were analyzed, including four wastewater treatment plants from four cities (n=319), and 7 local neighborhood collector sewers in Córdoba city (n=689). Serum and/or stool samples from patients suspected of HEV infection were also analyzed (n=48). HEV molecular detection and viral load quantification were performed by real time RT-qPCR, and genetic characterization by two RT-Nested PCRs (targeting partial ORF-1 and ORF-2 genomic regions), sequencing and phylogenetic analysis. Fifty-three (5.3%) wastewater samples were RNA-HEV positive by real time RT-qPCR, with variations according to the location and year (0.0% - 21.6%). Out of these, ORF-2 genomic region was amplified in 20 samples (37.7%) and ORF-1 partial region in 12 (22.6%), and eighteen sequences were obtained. Throughout the study period, two (4.2%) HEV confirmed infections were reported, and one sequence was obtained. Phylogenetic analyses for both genomic regions showed that all the isolates were genotype HEV-3 clade abchijklm. Our study detected HEV in wastewater over a six-year period, despite a low number of clinical cases, emphasizing WBE as a valuable tool that complements clinical surveillance, by detecting pathogens' presence; identifying their transmission, circulation dynamics and excretion hotspots; and revealing changes in their genomic diversity.